Isolation and characterization of an iodide bridged dimeric palladium complex in carbonylation of methanol - Tonde, S. S.; Kelkar, Ashutosh A.; Bhadbhade, Mohan M.; Chaudhari, Raghunath V. (Journal of Organometallic Chemistry, 2005)
Palladium-catalyzed carbonylation of methanol in presence of iodide promoters was investigated. Iodide bridged palladium dimeric complex, [PPh3CH3](2)[Pd2I6] was isolated from the carbonylation reaction mixture and characterized using X-ray crystallography. Reaction mechanism was proposed based on IR and UV spectroscopic characterizations of catalytic species involved in the catalytic cycle. The isolated dimeric palladium species, [Pd2I6](2-) underwent carbonylation to give monomeric species [PdI3CO](-) at atmospheric pressure of carbon monoxide. It was also observed that PPh3 plays an important role to avoid catalyst deactivation at higher temperatures. Turnover frequency (TOF) of 1052 h(-1) was achieved using Pd(OAC)(2)-HI-PPh3 catalyst system at 175 degrees C. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: dirneric palladium; IR spectroscopy; methanol carbonylation; palladium catalyst; reaction mechanism; UV